ANALISIS TINGKAT PENGETAHUAN DAN SIKAP SISWI TERHADAP ANEMIA DAN DISTRIBUSI TABLET TAMBAH DARAH PROGRAM DI SMAN 11 PALEMBANG DAN SMAN 1 GELUMBANG MUARA ENIM SUMATERA SELATAN - Ahmad Sadiq; Sartono Sartono (Media Keperawatan:Politeknik Kesehatan Makassar, 2021)
The results of the 2018 Basic Health Research (Riskesdas) show that the prevalence of anemia in women aged 15-24 years has the highest prevalence, namely 84.6% (Riskesdas, 2018). This study aims to obtain a description of the characteristics, level of knowledge and attitudes of anemia in students and to obtain information about the implementation of the distribution of the Blood Plus Tablet (TTD) program at SMU Negeri 11 Palembang and SMA Negeri 1 Gelumbang Muara Enim, Province of South Sumatra in 2020. The research design included analytic descriptive research with cross-optional design. The population in this study were all class X, XI and XII students with the status of active students who were recorded from absences in both SMA, totaling 1455 students. Samples were taken using purposive sampling technique, namely all populations who met the criteria, namely students who were registered at SMAN 11 Palembang and SMA Negeri 1 Gelumbang and participated in filling out and sending back the research questionnaire online. The data analysis used was univariate analysis and bivariate analysis. To obtain differences in data variations between the two independent groups, namely the average level of student knowledge of anemia in SMA Negeri 11 Palembang and SMA Negeri 1 Gelumbang, an independent sample test was carried out. The number of samples in this study were 508 respondents consisting of 163 students of SMA Negeri 11 Palembang Senamyal and SMA Negeri 1 Gelumbang as many as 345 students. Univariate analysis showed that the respondents' average body weight was 48.6 kg and height 156 cm. Based on BMI, most of the respondents were 87% or 442 female students in the thin category. The knowledge level of anemia with a sufficient category had the highest percentage of 64.8%. Most of the respondents 91.9% stated that they had never had their Hb checked independently. The same thing for Hb checks carried out by the school as many as 84.8% of respondents never checked Hb. As many as 79.9% of respondents in both high schools stated that they received bloodSupplemented tablets and most of the 77% respondents received information about anemia prevention in schools.Based on the statistical test table, the average level of knowledge for SMA Negeri 11 Palembang is 71.87 with a standard deviation of 8.908, while for SMA Negeri 1 Gelumbang the average level of knowledge is 72.68 with a standard deviation of 9.068. The statistical test results obtained p value = 0.347 where> 0.05, it can be concluded that there is no significant difference to the average level of knowledge of students at SMA Negeri 11 Palembang and SMA Negeri 1 Gelumbang. Based on the statistical test table, the difference in the average attitude of getting the attitude score for SMA Negeri 11 Palembang students was 18.21 with a standard deviation of 20.058, while for SMA Negeri 1 Gelumbang students the attitude score was 10.01 with a standard deviation of 2.050. The results of the statistical value obtained by the value of p = 0.306 where p> 0.05, it can be concluded that there is no significant difference in the average value of attitudes among students of SMA Negeri 1 Gelumbang and SMA Negeri 11 Palembang.